Some Kinematic Variables And Special Motor Abilities And Their Relationship To The Effectiveness Of Performing The Skill Of The Front Drop Kick From Jumping And Stability For Badminton Players - et. al., Yousif Gabbar Luaibi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of the research lies in knowing the real role of some kinematic variables and special kinetic abilities and their relationship to the effectiveness of the front-kick skill performance of jumping and stability in order to reach the technique, good and accurate achievement, and upgrading the level of the player. Next: Do the kinematic variables and special kinematic abilities have an important role in the effective performance of the front dropped blow skill of jumping and stability in the flying feather in the research sample? The research sample, as well as identifying the correlation relationship between the values ​​of some kinematic variables and the kinetic abilities of the effectiveness of the front drop strike skill of jumping and stability in the research sample. Research sample of governorate players Basra Badminton for the competitive season 2020-2021 for the category of applicants, which number (10) players. The fourth chapter is a presentation, analysis and discussion of the researcher's findings. The conclusions were: a significant correlation relationship appeared between the variables (the angle of the elbow joint, the angle of the knee joint, the angle of the shoulder joint, and the height of the hip joint) on the one hand, and the effectiveness of performing the front drop skill from jumping on the other hand. A non-significant correlation was also shown between the variables (the ankle joint angle, the highest height of the feather at the moment the racket touched the feather, the highest height of the feather after launch, the height of the feather over the net) on the one hand, and the effectiveness of the skill of the front drop hitting from jumping on the other hand, and recommendations included confirmation To direct the players to pay attention to the angles of the joints of the body during the technical performance of badminton skills, to use the kinematic analysis programs by coaches and specialists in this field to correct some technical errors of the players that are not seen with the eye due to the speed of movement, as well as to emphasize the increase in the tide in the joints of the body the moment the racket touches for the feather.